Biodegradação de óleo diesel por candida lipolytica em água do mar. - Souza, Fabiana América Silva Dantas de (2009)
The biodegradation of hydrocarbons by natural population of microorganism represents one of the primary mechanisms by which diesel oil and others hydrocarbons pollutants are eliminated or transformed in the environment. It is generally accepted today that petroleum hydrocarbon, can be degraded by microorganisms as long as a few factors, such as nutrients, organic compound bioavailability, pH and temperture are controlled and optimized. In this study biodegradationof diesel oil by Candida lipolytica in sea water supplemented with nitrogen and phosphorus sources was investigated in skake flask fermentation scale. A set of three full factorial designs was carried out to investigate the effects and interactions of pH and the seawater, diesel oil, urea, ammonium sulfate and potassium dihydrogen orthophosphate concentrations on the C.lipolytica growth, the emulsification activity and the surface tension of the free cell broth. The biodegradation of diesel oil was confirmed through four laboratory experiments using: (1) seawater + diesel oil; (2) distilled water + diesel oil; (3) seawater + corn oil and (4) distilled water + corn oil. The best result for 5% (v/v) diesel degradation was obtained at condition 1, using seawater supplemented with 1,0% (p/v) of ammonium sulfate and 1,0 % (p/v) of potassium dihydrogen orthophosphate. In this condition, after 96 h, the pH, the salinity, the surface tension and the emulsification activities to emulsions with corn oil and with motor oil were equal to 9.47, 44 , 46.63 mN/m, 5.49 e 6.00 UAE, respectively. Whereas C.lipolytica has potential application in biotechnological process, the production medium conditions and bioemulsifiers and biosurfactants produced are candidates to be optimized and used in bioremediation of marine environments contaminated by diesel and other oil products.